2010
DOI: 10.1088/1478-3975/7/2/026009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory neurons modulate spontaneous signaling in cultured cortical neurons: density-dependent regulation of excitatory neuronal signaling

Abstract: Cortical neuronal activity depends on a balance between excitatory and inhibitory influences. Culturing of neurons on multi-electrode arrays (MEAs) has provided insight into the development and maintenance of neuronal networks. Herein, we seeded MEAs with murine embryonic cortical/hippocampal neurons at different densities (<150 or >1000 cells mm(-2)) and monitored resultant spontaneous signaling. Sparsely seeded cultures displayed a large number of bipolar, rapid, high-amplitude individual signals with no app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(63 citation statements)
references
References 23 publications
9
54
0
Order By: Relevance
“…We observed stimulation or suppression of spontaneous signaling using native or inverted Biological Signal, indicating that neuronal subpopulations were opposingly affected depending upon signal orientation. Inhibition of spontaneous signaling suggests a predominant impact on inhibitory neurons, consistent with the prior demonstration that GABAergic neurons are responsible for synchronized bursts in mature signal patterns (19,22). …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…We observed stimulation or suppression of spontaneous signaling using native or inverted Biological Signal, indicating that neuronal subpopulations were opposingly affected depending upon signal orientation. Inhibition of spontaneous signaling suggests a predominant impact on inhibitory neurons, consistent with the prior demonstration that GABAergic neurons are responsible for synchronized bursts in mature signal patterns (19,22). …”
Section: Resultssupporting
confidence: 87%
“…Images present representative signal profiles for all recorded channels. Prior studies using combinations of excitatory and inhibitory neuronal antagonists have confirmed synaptic origin of signal in these cultures (17,19,22). …”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…Other appropriate software is available [1,28]. Networks were stimulated using a 1sec digitized synaptic signal 1mV in amplitude as in our prior studies [3,4,27]. Output was graphed and analyzed in Excel.…”
Section: Recording Of Network Activitymentioning
confidence: 99%
“…After culturing for 1 month to allow maturation of networks (confirmed by development of spontaneous signal streams rich in complex bursts [27], networks were segmented into two equivalent halves by slicing across the petri dish with a scalpel. This segmentation was not essential, but served to generate two independent "hemispheres."…”
Section: Recording Of Network Activitymentioning
confidence: 99%